2008
DOI: 10.1016/j.ijrobp.2008.06.774
|View full text |Cite
|
Sign up to set email alerts
|

Initial Efficacy Results of RTOG 0319: Three Dimensional Conformal Radiation Therapy (3D-CRT) Confined to the Region of the Lumpectomy Cavity for Stage I/II Breast Carcinoma

Abstract: Purpose-This prospective study (Radiation Therapy Oncology Group 0319) examines the use of three-dimensional conformal external beam radiotherapy (3D-CRT) to deliver accelerated partial breast irradiation (APBI). Initial data on efficacy and toxicity are presented.Methods and Materials-Patients with Stage I or II breast cancer with lesions≤3 cm, negative margins and with≤3 positive nodes were eligible. The 3D-CRT was 38.5 Gy in 3.85 Gy/fraction delivered 2×/day. Ipsilateral breast, ipsilateral nodal, contralat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…A three‐year report from a Canadian multicenter study on APBI using 3D CRT ( 3 ) showed acceptable toxicity and cosmesis with excellent control and disease‐free survival. Initial efficacy results (locoregional control and toxicity) of RTOG 0319 using 3D CRT to deliver APBI ( 4 ) were comparable with other published studies with similar fallow‐up. These preliminary data support continued accrual to APBI trials, but also emphasize the need for further follow‐up to fully evaluate long‐term tumor control and late toxicity.…”
Section: Introductionsupporting
confidence: 76%
“…A three‐year report from a Canadian multicenter study on APBI using 3D CRT ( 3 ) showed acceptable toxicity and cosmesis with excellent control and disease‐free survival. Initial efficacy results (locoregional control and toxicity) of RTOG 0319 using 3D CRT to deliver APBI ( 4 ) were comparable with other published studies with similar fallow‐up. These preliminary data support continued accrual to APBI trials, but also emphasize the need for further follow‐up to fully evaluate long‐term tumor control and late toxicity.…”
Section: Introductionsupporting
confidence: 76%
“…As mentioned above, 3D‐CRT represented the initial modern external beam PBI technique. Initial acute toxicity data from William Beaumont Hospital were promising as were initial results of RTOG 0319 . However, concerns have been raised about late toxicity (fibrosis, deterioration of cosmetic outcomes) .…”
Section: Discussion/observationsmentioning
confidence: 99%
“…The results presented here are concordant with the American Society of Breast Surgeons MammoSite Registry Trial which found a 3 year AF rate of 0.36% with no RNF data presented 11. Radiation Therapy Oncology Group trial 0319, which evaluated the efficacy of 3‐D CRT as a method for APBI, reported a 4‐year lymph node failure rate of 2%, which is somewhat higher than the rate in our series 12. However, a previous review of 199 patients who received interstitial APBI from our institution with 10‐year follow‐up produced RNF rates of 0%, 1.7%, and 5.9% in patients who were categorized as suitable, cautionary, and unsuitable, respectively, which was slightly higher but comparable to our current findings 13.…”
Section: Discussionmentioning
confidence: 99%